An evaluation of the CARES® Dementia Basics Program among caregivers. (3rd October 2016) - Pleasant, Michelle L.; Molinari, Victor; Hobday, John V.; Fazio, Sam; Cullen, Nancy; Hyer, Kathryn
ABSTRACT: Background: In 2014, the state of Oregon established Oregon Care Partners to provide high quality, free training to all dementia caregivers. This study evaluated participants' changes in knowledge, sense of competency in dementia caregiving, and ability to identify person-centered caregiving techniques after completing CARES® Dementia Basics online program, one of the educational resources available through this initiative. Methods: A convenience sample of informal and formal caregivers ( N = 51) provided data at three points in time; pre-test, post-test, and a follow-up test after an additional 30-day period to determine sustained changes in knowledge, sense of competency, and person-centered care. Results: From pre-test to post-test, modest improvements were detected in sense of competence in performing dementia care ( ps < 0.01) and dementia-based knowledge, F (2, 150) = 7.71, p < 0.001, a multivariate effect size of w 2 = 0.09. Even though improvements in sense of competency were not universal, three out of five individual items demonstrated positive growth from pre-test to post-test as well as four out of the five items from pre-test to follow-up test. Importantly, gains observed in dementia-based knowledge from pre-test to post-test were largely maintained at the 30-day follow-up. No significant changes were found in the correct identification of person-centered techniques after the training F (5, 150) = 1.63, p = 0.19. Conclusions: Future research should investigate how best to maintain educational interventions within the caregiving environment and to assess subsequent skill change.